The Future of Last-Mile Logistics: Pathways Toward Sustainable E-Commerce - Budiyanto, Albert; Faisal, Ahmad; Putra, Dimas Endrawan; Mintje, Quirina Ariantji Patrisia (Logistica : Journal of Logistic and Transportation, 2024)
The exponential growth of e-commerce has intensified challenges in last-mile delivery logistics, making sustainability a critical priority for researchers, policymakers, and industry practitioners. This study synthesizes existing literature on sustainable practices in last-mile logistics, focusing on economic, environmental, social, and technological dimensions. A narrative review approach was employed, drawing from academic databases such as Scopus, Web of Science, and Google Scholar. Literature was selected using targeted keywords and inclusion criteria to ensure comprehensive coverage of practices ranging from cost efficiency strategies to technological innovations. The results reveal that sustainable logistics practices, such as electric vehicle adoption, route optimization, and crowd logistics, can reduce operational costs, improve customer satisfaction, and decrease carbon emissions. However, disparities between developed and developing countries highlight systemic challenges, including inadequate infrastructure, limited regulatory support, and varying consumer preferences. Social outcomes, including the welfare of couriers and improvements in urban air quality, emphasize the broader societal benefits of sustainability, though labor protections remain underexplored in the literature. Technological advances, particularly GIS-based systems and autonomous vehicles, offer transformative potential but require supportive policy frameworks for effective implementation. The discussion highlights the importance of systemic factors—policy, regulation, and infrastructure—in shaping adoption. This review concludes that sustainable last-mile logistics is essential for aligning economic growth with ecological responsibility and social equity, recommending targeted policies, cross-sector collaboration, and longitudinal research to address current limitations.